Pengaruh Kejelasan Sasaran Anggaran, Pengendalian Akuntansi dan Sistem Pelaporan terhadap Akuntabilitas Kinerja Instansi Pemerintah dengan Kepatuhan Terhadap Regulasi sebagai Variabel Pemoderasi - Helin Gustri Mulya; Eka Fauzihardani (Universitas Negeri Padang, 2022)
This research aimed on analyzing of budget goal clarity, accounting controls and systems reporting for performance accountability government agencies with regulatory compliance as moderating variable. In this research, officials who served as a head agency, finance program and evaluation chiefs, treasurers and finance staff at 30 SKPD in Sungai Penuh district were as a respondent . The sampling method uses purposive sampling, while the data processing method uses multiple linear regression analysis. The amount of samples in this study was 90 respondents. The statistic testing result showed that accounting controls and systems reporting have no effect on performance accountability of government agencies, but variable budget goal clarity have positive significant effect on performance accountability of government agencies. The regulatory compliance as moderating variable could moderated the relationship between variable budget goal clarity, controls accounting and systems reporting with performance accountability of government agencies Sungai Penuh. Suggestions for further research to increase the sample and add new variables that may have an effect.